Optimization of blast mitigating sandwich structures with fiber-reinforced face sheets and PVC foam layers as core - Alanbay, B.; Batra, R.C. (Thin-walled structures, 2022)
It is challenging to find lightweight blast mitigating structures for protecting civilian and military infrastructure. Here we synthesize a surrogate optimization algorithm with a numerical technique to analyze dynamic deformations of sandwich structures with fiber-reinforced face sheets perfectly bonded to eight PVC foam layers, and to simultaneously minimize the structural mass and maximize its blast mitigating capabilities. The eighteen variables to be optimized are thicknesses of the two face sheets and of the eight foam layers and the lay-up of the core layers such that either the total reaction force transmitted to a rigid substrate or the deflection of the back face is minimized. The deformations of the structure and the pressure produced by detonating a charge are simulated using the commercial finite element software ABAQUS. The progressive damage and delamination between adjacent layers of the face sheets and their debonding from the core are, respectively, considered using a user-defined subroutine and a cohesive zone model. It is found that for an optimum structure, the mass density and the elastic modulus of the core layers does not continuously vary through the thickness, i.e., the core is not comprised of a functionally graded foam. The low (high) density foam layers minimize the total reaction force (the back face deflection). •Optimization of sandwich structures for blast mitigation and minimum mass.•Damage initiation and propagation due to Hashin’s failure criteria for 3-D deformations.•The foam core not functionally layered for optimum geometries.•Computed maximum strain rate in a foam is about 1200/s.